Architectural approaches to the design of teenager rehabilitation and reintegration centers - Akhmadishina Elina R.; Korotkova Svetlana G. (Архитектон, 2025)
This article discusses the problem of designing centers for the restoration of mental and physical health of adolescents. Currently there is a need for specialized centers that would help teenagers to socialize in society and acquire the necessary skills for life. The purpose of this work is to identify design factors and develop basic techniques and approaches to the design of adolescent reintegration and rehabilitation centers. Current research in the organization of space for the integration of children into society, their treatment and upbringing is overviewed. The theoretical framework derived from existing centers served as a basis for identifying architectural design techniques and approaches to the design of centers for the reintegration and rehabilitation of children and adolescents, including adaptability, permeability of spaces, organization of private areas, and navigation elements.